Efficacy of Endoscopic Middle-meatus Antrostomy in Chronic Maxillary rhinosinusitis. A Prospective - Mansoor Alam; Siyyar Ahmad; Naveed Khan; Ihtisham Ul Khaliq; Hamza -; Abdul Aziz (Proceedings, 2025)
Introduction: Chronic maxillary sinusitis(CMS) significantly impacts quality of life, requiring effective interventions. Middle meatal antrostomy (MMA) is a widely performed surgical procedure, but its outcomes and complications need further evaluation.